Mechanisms of Timing, Timbre, Repertoire, and Entrainment in Neuroplasticity: Mutual Interplay in Neonatal Development - Loewy, Joanne; Jaschke, Artur C. (Frontiers in Integrative Neuroscience, 2020)
Neonatal brain development relies on a combination of critical factors inclusive of genetic predisposition, as well as the conditions of the pre and post neonatal environment. The conditions of the infant brain in its most vulnerable state and the impact that physiological elements of music, silences and sounds can make in the earliest stages of brain development are critical. This article will present and support research that has hypothesized conditions of music therapeutic applications in an effort to validate models of neurobehavioral care that have optimal conditions for growth, inclusive of recommendations leading toward the enhancement of self-regulatory behaviors.